The effect of job design and job description on employees’ performance - Reflin Ibrahim, Abd. Rahman Pakaya,; Gai Sin, Liem (Opción, 2019)
This study aims to determine the effect of partial job design on the performance of employees in the Gorontalo City Population and Civil Registration Service. The research approach used is a quantitative method. Data analysis used multiple regression analysis. The results of this study indicate that Job design does not have a positive and significant effect on employee performance with a regression coefficient of 16.1%. It can be concluded that partially the job design does not have a significant effect on the performance of employees in the Gorontalo City Population and Civil Registration Service.